Spectroscopic data of 3-O-acetyl-betulinic acid: an antitumor reagent - Ahmad @ Amat, Faujan; Ghaffari-Moghaddam, Mansour; Basri, Mahiran; Abdul Rahman, Mohd Basyaruddin (Chemic Publishing Company, 2010)
In this paper, the spectroscopic data of the 3-O-acetyl betulinic acid is reported. This compound was prepared by enzymatic reaction of betulinic acid and acetic anhydride in the presence of lipase from Candida antarctica (Novozem® 435) at 54oC for 20 h in 79.3 % yield.